2011
DOI: 10.3168/jds.2010-3831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding different levels of dietary fiber through the addition of corn stover on nutrient utilization of dairy heifers precision-fed high and low concentrate diets

Abstract: The objective of this experiment was to assess the effects of manipulating dietary fiber by replacing corn silage (CS) with lower quality forage as corn stover (CST) when used in high concentrate (HC) and low concentrate (LC) diets for precision-fed dairy heifers. Eight Holstein heifers (335.6 ± 7.41 kg of body weight) were randomly assigned to 2 levels of concentrate: HC (20% forage) and LC (80% forage), and to a forage type sequence [0% of forage as corn stover (CST), 100% corn silage (CS); 20% CST, 80% CS; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
41
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 42 publications
(88 reference statements)
31
41
7
Order By: Relevance
“…This allowed cellulose to be retained longer and be further digested in the LF diets. Starch digestibility seems to be increased by higher retention time of LF diets (Lascano and Heinrichs, 2011), as well as by a more numerous amylolytic bacteria population associated with this type of diet (Brown et al, 2006). These results are in agreement with observations in the present study and with the ones reported in limit-fed sheep and cattle (Colucci et al, 1989;Murphy et al, 1994).…”
Section: Diet Digestibilitysupporting
confidence: 96%
See 3 more Smart Citations
“…This allowed cellulose to be retained longer and be further digested in the LF diets. Starch digestibility seems to be increased by higher retention time of LF diets (Lascano and Heinrichs, 2011), as well as by a more numerous amylolytic bacteria population associated with this type of diet (Brown et al, 2006). These results are in agreement with observations in the present study and with the ones reported in limit-fed sheep and cattle (Colucci et al, 1989;Murphy et al, 1994).…”
Section: Diet Digestibilitysupporting
confidence: 96%
“…Total-tract digestibility of DM, OM, NDF, ADF, and cellulose were lower for HF diets. Apparent DM and OM dC were similar to results observed by Lascano and Heinrichs (2011) when heifers were fed LF or HF diets composed of a combination of 40 or 80% CS and corn stover. Digestibility of NDF and ADF followed a similar pattern as DM and OM apparent digestibility (Zanton and Heinrichs, 2009;Lascano and Heinrichs, 2011).…”
Section: Diet Digestibilitysupporting
confidence: 85%
See 2 more Smart Citations
“…Marsetyo et al (2006) reported that supplementations of barley and barley plus protein increased microbial protein synthesis and efficiency of microbial protein synthesis in steers. High concentrate supplementation for low quality forage based diet elevated microbial protein synthesis in dairy heifers (Lascano and Heinrichs, 2011). Moorby et al (2006) suggested that increasing microbial protein synthesis supported enhancing milk yield in dairy cows when they fed on diets with lower forage to concentrate ratio.…”
Section: Microbial Nitrogen Synthesismentioning
confidence: 99%